1992
DOI: 10.1046/j.1365-313x.1992.t01-32-00999.x
|View full text |Cite
|
Sign up to set email alerts
|

A Brassica napus gene family which shows sequence similarity to ascorbate oxidase is expressed in developing pollen. Molecular characterization and analysis of promoter activity in transgenic tobacco plants

Abstract: SummaryThe genomic clone named BplO contains a member of a small pollen-specific gene family of 9. napus. The expression of the BplO gene family is maximal in early binucleate microspores and declines considerably in mature trinucleate pollen. Homologues of the BplO genes are expressed in the pollen of other plant species. The pollen-specific expression of the gene contained in the genomic clone was confirmed in tobacco plants transformed with a chimeric BplO promoter/GUS construct. A promoter fragment of 396 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(6 citation statements)
references
References 31 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…, 1996), SERINE CARBOXYPEPTIDASE II‐3 PRECURSOR ( CP‐MII.3 ), a gibberellic acid‐induced gene that is involved in grain development in barley (Dal Degan et al. , 1994), and an ascorbate oxidase gene, which is expressed in developing pollen of Brassica napus (Albani et al. , 1992).…”
Section: Resultsmentioning
confidence: 99%
“…, 1996), SERINE CARBOXYPEPTIDASE II‐3 PRECURSOR ( CP‐MII.3 ), a gibberellic acid‐induced gene that is involved in grain development in barley (Dal Degan et al. , 1994), and an ascorbate oxidase gene, which is expressed in developing pollen of Brassica napus (Albani et al. , 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Most data are available for late pollen promoters. These include petunia chiA [5], tomato LAT52 and LAT59 [4,6], rapeseed Bp10 [7], maize Zm13 [8,9] and tobacco NTP303 [10]. In Arabidopsis these include the TUA1 [11], AtPTEN1 [12], AtSTP6 [13], AtSTP9 [14] and the late vegetative cell-specific AtVEX1 [15] promoters.…”
Section: Introductionmentioning
confidence: 99%
“…Because the FIL2 gene is not expressed in a homeotic mutant, deficiens, and has a CArG box, the binding motif of MAD S box proteins, in its promoter region, it is strongly suggested that FIL2 is a target of the DEFICIENS gene product. The ascorbate oxidase gene of Brassica napus has a CArG box in its promoter [2]. This gene is specifically expressed in pollens at later stages of the maturation process.…”
Section: Floral Organ Growth and Differentiationmentioning
confidence: 99%